Communication in Traditional Leadership of the Yogyakarta Sultanate: Dimensions of Power and Social Influence - Surahman, Sigit; Rully (Future Science, 2025)
This study examines the role of communication in the traditional leadership of the Yogyakarta Sultanate, focusing on the dimensions of power and social influence. The context of the study is Sultan Hamengku Buwono X's communication practices in maintaining symbolic and political legitimacy through cultural rituals, as well as the Sabda and Dawuh (Islamic Proclamation). A phenomenological approach and a critical paradigm were used in this study. Data were collected through in-depth interviews, direct observation, and document analysis, such as the Sabda and Dawuh Raja (Islamic Proclamation) column in print and electronic media. The findings indicate that: (1) traditional communication through customary rituals and direct Sabda serves as a powerful mechanism for legitimizing vertical power; (2) the communication structure within the palace is generally top-down; (3) there are elements of symbolic dialogue between the Sultan and the community, reflecting a traditional democratic communication style with low dominance and high sociability. Communication in the leadership of the Yogyakarta Sultanate serves a dual function: establishing symbolic and socio-cultural legitimacy; and simultaneously creating profound social influence through symbolism and inherited cultural values. This study suggests further exploration of the influence of modern digital communication and the role of the younger generation in developing traditional power dialogue in Yogyakarta.